Planning for a successful digitization of library material: A theoretical perspective - Zondi B., Bongiwe C. Nyide, Wellington B. (Opción, 2019)
This paper aims to plan a successful digitization for academic, public or special libraries with the aid of a survey method as a descriptive research method.It is clear that when embarking on a digitization process a lot has to be taken into account over and above the financial resources. The people involved in the management of the process must identify the material to be sourced and digitized, they must know who is likely to use the material. Also, it is important to look at the qualities and capabilities of the staff that will be involved in the digitization process/project.